(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
قمنا بتحديد محتوى بعض العناصر الكيميائية (Fe, Ca, Ba, Sr ) وكذلك محتوى SO4-2 داخل مياه البئر المرافقة للنفط الخام السوري وذلك في حقول شركة الفرات للنفط كما قمنا بدراسة ترسب هذه العناصر على هيئة كبريتاتها. أعطت نتائج تحديد العناصر المذكورة أعلاه، باستخدام تقانة الامتصاص الذري محتويات كمية تفوق المستوى المسموح به وهذا ما أدى إلى سقوطها على هيئة رواسب الكبريتات: CaSO4-FeSO4 -BaSO4-SrSO4. وكان الخطأ المعياري النسبي المرتكب قي تحديد تراكيز العناصر المذكورة أعلاه ضمن مجال خطأ التقانة المستخدمة. We have determined the content of certain chemical elements (Sr, Ba, Ca, and Fe) and SO4-2content within well water accompanying the Syrian crude oil in the fields of Al-Furat Petroleum Company. We have also studied the precipitation of these elements in the form of their sulfates. The results of determining the above mentioned elements using the atomic absorption technology gave quantitative contents which exceed the permitted level, leading to their falling as sulfate precipitates: CaSO4, FeSO4, BaSO4, SrSO4. Relative standard deviation committed in determining the concentrations of the above mentioned elements was within the error range of the technology used.